Measurement of public space justice in traditional villages with coexistence of old and new based on villagers’ perceptions - Bingbin Tian; Yunyuan Deng; Mingcheng Jiang (PLoS ONE, 2026)
Rural spatial justice studies lack frameworks addressing rural–urban contextual gaps. We bridge this by proposing a three-dimensional model (recognition-distribution-participation) to quantify villagers’ spatial justice perceptions in transitional villages with old-new coexistence. Using 314 surveys across Zhushan (Hunan) and Dabitou (Guangxi), structural equation modeling (SEM) confirms the model explains 63% of variance—highlighting the interconnected nature of recognition, distribution, and participation in shaping justice perceptions, a nuance that single-dimension approaches may overlook.Key results reveal: Distributive justice (e.g., infrastructure equity) dominantly shapes perceptions (β = 0.45);Recognition justice is mediated by cultural symbols but constrained by weak revitalization; Participatory justice remains critically low due to governance deficits. Qualitative contrasts suggest how endogenous governance in Zhushan may strengthen recognition, while capital-driven monopolies in Dabitou appear to suppress participation.This study advances rural geography by:Adapting urban-centered justice theory to rural transitions;Providing a preliminary metric for spatial equity assessment in similar aging rural contexts. Findings offer context-specific insights for optimizing public space allocation in transforming villages facing comparable demographic challenges.